أثر اكتساب مهارات التواصل الشفوي في تحصيل تلاميذ الصف الرابع الأساسي في مادة العلوم والتربية الصحية دراسة شبه تجريبية في مدينة اللاذقية (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
تعد مهارات التواصل الشفوي (التحدث والاستماع) من أهم المهارات الحياتية التي يجب أن يتقنها الإنسان العادي بشكل عام والمتعلم بشكل خاص، لأنها تعد الركيزة الأساسية في مهارات اللغة الأربع (الاستماع والتحدث، والقراءة والكتابة)  في ظل القرن الحادي والعشرين، بكل معالمه وتحدياته وسماته في مجال ثورة الاتصال، وما يتبعها من تسلط ثقافي وفكري على عقل الصغير والكبير والأمي والمتعلم. تهدف الدراسة الحالية إلى معرفة أثر اكتساب مهارات التواصل الشفوي (التحدث والاستماع) في تحصيل تلاميذ الصف الرابع الأساسي في مادة العلوم والتربية الصحية, ولتحقيق أهداف البحث تمّ أخذ عينة عشوائية بحجم /80/ تلميذاً من تلاميذ الصف الرابع الأساسي بمدينة اللاذقية, وطبق عليهم بطاقة ملاحظة أداء مهارات التواصل الشفوي (التحدث والاستماع) واختبار تحصيلي قبل البدء بتطبيق البرنامج التدريبي كاختبار قبلي, وبعد تطبيق البرنامج التدريبي كاختبار بعدي. وانتهى البحث إلى النتائج الآتية: - وجود فروق بين متوسط درجات التلاميذ في التطبيق القبلي لبطاقة ملاحظة المهارات ومتوسط درجات التلاميذ في التطبيق البعدي لبطاقة ملاحظة المهارات, وهذه الفروق لصالح درجات التلاميذ في التطبيق البعدي. - وجود فروق بين متوسط درجات المجموعة التجريبية ومتوسط درجات المجموعة الضابطة عند مستوى دلالة (0,05) بعد تطبيق البرنامج التعليمي على اختبار التحصيل الدراسي في القياس البعدي، وهذه الفروق لصالح درجات المجموعة التجريبية. Oral communication skills (speaking and listening) are of the most important life skills that must be mastered by an ordinary man, and a learner in general, because it is a cornerstone in the four language skills (listening, speaking, reading and writing) in the twenty-first century, with all its features, challenges and characteristics in the area of communications revolution, and its intellectual and cultural highlights on the mind of the young and the old, the illiterate and learners. The present study addresses the impact of oral communication skills (speaking and listening) in the attainment of the fourth basic grade students in science and health education, and to achieve the research objectives a random sample of / 80/pupils (fourth grade) in the city of Latakia was taken, who underwent the notice card of oral communication skills performance (speaking and listening), an achievement test before applying the training program as a pre-test, and after applying the training program as a post-test. The search concluded with the following results: -   There are differences between the average scores of students in the pre-application of note card of skills and students' average scores in the post-application of note card of skills, and these differences are in favor of students in post-application. -   There are differences between the average of the experimental group degrees and that of the controlling group degrees at the (0,05) indication level after applying the educational programme to the academic acquisition test in the dimensional measure.